(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. I precedenti giurisprudenziali - 3. Un nuovo ruolo per i giudici tunisini? - 4. La tutela dei diritti e delle libertà: tra comparazione e fiqh - 5. Profili comparatistici. Il processo di rettifica del genere in una pronuncia della Corte d’appello di Beirut - 6. Considerazioni conclusive. A landmark decision concerning gender rectification in Tunisia: the right to a private life between comparative law, international law and fiqh ABSTRACT: The decision of the Tribunal of Tunis, concerning gender rectification in public registries of a transgender FtM person who underwent sex reassignment treatment, is an example of innovative case law. The judgment, changing the previous case law, is characterized by the use of the comparative method, so that, in the grounds for ruling, legal principles from different foreign jurisdictions and the fiqh coexist. Specifically, the Tribunal of Tunis, showing an open and dialogical approach to other jurisdictions and legislations of the globe, has consecrated the fundamental human right of gender rectification in public registries, rarely recognized in other Arab countries.